Ethical issues experienced during palliative care provision in nursing homes. (September 2019) - Muldrew (née Preshaw), Deborah HL; McLaughlin, Dorry; Brazil, Kevin
Background: Palliative care is acknowledged as an appropriate approach to support older people in nursing homes. Ethical issues arise from many aspects of palliative care provision in nursing homes; however, they have not been investigated in this context. Aim: To explore the ethical issues associated with palliative care in nursing homes in the United Kingdom. Design: Exploratory, sequential, mixed-methods design. Methods: Semi-structured interviews with 13 registered nurses and 10 healthcare assistants (HCAs) working in 13 nursing homes in the United Kingdom were used to explore ethical issues in palliative care. The 'Ethical Issues in Palliative Care for Nursing Homes' instrument was used to measure the frequency and level of distress arising from ethical issues through a cross-sectional survey with 69 registered nurses and 129 healthcare assistants. Data collection occurred between December 2014 and November 2015. Ethical considerations: Ethical approval was granted by Queen's University's School of Nursing and Midwifery Research Ethics Committee and governance sought from each nursing home's manager. Findings: The interviews revealed three themes: ethical issues in practice; relational issues; and organisational issues. No significant differences between registered nurses and healthcare assistants were evident, confirming the patterns emerging from the interviews. Relational issues, primarily issues with residents and families, occurred most frequently and caused greater distress. Conclusion: The shared environment is key in the experience of ethical issues; therefore, multidisciplinary education is needed for ethical decision making in palliative care. Addressing staff knowledge and service organisation may reduce ethical issues locally and provide a benchmark for global change.